A one-dimensional Ag NW@NiCo/NiCo(OH)2 core–shell nanostructured electrode for a flexible and transparent asymmetric supercapacitor. Issue 14 (15th March 2019) - Liu, Junyan; Shen, Gengzhe; Zhao, Sirou; He, Xin; Zhang, Chi; Jiang, Tinghui; Jiang, Jiayi; Chen, Bohua
Abstract : One-dimensional Ag nanowire@NiCo/NiCo(OH)2 core–shell nanostructures with a tunable composition are constructed by electrodeposition, showing potential applications in transparent and flexible supercapacitors. Abstract : Flexible and transparent electrodes based on one-dimensional Ag nanowire@NiCo/NiCo(OH)2 core–shell nanostructures with a tunable composition were fabricated by electrodeposition. The highly conductive Ag nanowire (NW) network was considered as a current collector, and the NiCo/NiCo(OH)2 nanostructures could grow on the surface of the Ag NWs, providing active materials with the synergistic effect of Ni and Co elements. The core–shell nanostructures integrate the advantages of metallic NWs for effective charge transport, the NiCo alloyed layer for a stable structure, and NiCo(OH)2 for high electrochemical performance. The composite electrode with a transmittance of 54.3% delivers a high areal capacitance of 22.2 mF cm −2 at a current density of 0.1 mA cm −2, and an excellent capacitance retention rate of 91.9% at 100 mV s −1 after 5000 cycles. Furthermore, an asymmetric supercapacitor composed of the Ag NW@NiCo/NiCo(OH)2 cathode and the Ag NW/graphene anode achieves a maximum areal capacitance of 9.6 mF cm −2 at a current density of 0.2 mA cm −2, high energy density of 3.0 W h kg −1 and power density of 3.5 W kg −1 . The Ag NW@NiCo/NiCo(OH)2 core–shell nanostructured electrode shows great potential for flexible and transparent energy storage devices.